Relationships Between Cognitive Impairment, Knowledge and Attitudes Among Drug Misusers Undergoing an Islamic Therapy in Malaysia - Pei Lin, Lua (International Journal of Psychosocial Rehabilitation, 2017)
Studies on the relationship between knowledge and attitude (KA) and cognitive status of drug misuders are generally still limited in Malaysia. In particular, those who are seeking religious-based modalities to treat addiction problems. This study aimed to 1) determine the cognitive status and KA among drug addicts and 2) compare the KA of drug addicts with different cognitive status (regrouped into ”Good” and ”Poor”). Drug misusers who were undergoing the Islamic (Inabah) Therapy Module were enrolled from Pusat Rawatan Darul Taubah in Pasir Puteh, Kelantan. The Malay Sahlgrenska Academy Self – Reported Cognitive Impairment Questionnaire (SASCI – Q) and Drug – Related Knowledge, Attitudes and Belief (KA) Questionnaire were administered (higher scores indicating favourable cognitive and KA status). Data was analysed using SPSS 23, employing descriptive and non-parametric techniques. Thirty – seven male Muslim participants were recruited (age = 28.4 ± 7.0 years; single = 81.1%; PMR/SRP/LCE qualification = 45.9%; self-employed = 62.2%). Both cognitive status and KA were moderate, with mean of 66.2 ± 13.3 and 57.3 ± 12.5 respectively. Those who started addiction younger had worse cognitive status. With regard to KA, no significant difference was detected between respondents possessing different cognitive status (all p > 0.05). Nonetheless, the general trend demonstrated that those with higher cognitive status (median ≥ 66.2) reported relatively better knowledge (60.4 ± 16.9). More favourable knowledge and attitudes profiles were similarly exhibited by the group with higher cognitive status.